2020
DOI: 10.3390/electronics9050730
|View full text |Cite
|
Sign up to set email alerts
|

Robust ESD-Reliability Design of 300-V Power N-Channel LDMOSs with the Elliptical Cylinder Super-Junctions in the Drain Side

Abstract: The weak ESD-immunity problem has been deeply persecuted in ultra high-voltage (UHV) metal-oxide-semiconductor field-effect transistors (MOSFETs) and urgently needs to be solved. In this paper, a UHV 300 V circular n-channel (n) lateral diffused MOSFET (nLDMOS) is taken as the benchmarked reference device for the electrostatic discharge (ESD) capability improvement. However, a super-junction (SJ) structure in the drain region will cause extra depletion zones in the long drain region and reduce the peak value o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Even a small defect during manufacturing can cause considerable losses to the manufacturer. Electrostatic discharge (ESD) events [1][2][3][4][5][6][7][8][9][10] for integrated circuits (ICs) are the major hazard to reliability.…”
Section: Introductionmentioning
confidence: 99%
“…Even a small defect during manufacturing can cause considerable losses to the manufacturer. Electrostatic discharge (ESD) events [1][2][3][4][5][6][7][8][9][10] for integrated circuits (ICs) are the major hazard to reliability.…”
Section: Introductionmentioning
confidence: 99%
“…In the semiconductor area of research, a robust electrostatic discharge reliability design of an ultra-high voltage 300-V power n-channel lateral diffused MOSFETs, with elliptical cylinder super-junctions in the drain side, is given in [25]. The authors have concluded that this is a decent strategy and the human-body model capability of these ultra-high voltage n-channel lateral diffused MOSFETs could be successfully improved without altering the basic electrical properties or adding any extra cell area.…”
Section: Introductionmentioning
confidence: 99%